Giải phương trình sau: $\frac{5(x-1)+2}{6}$$-$$\frac{7x-1}{4}$$=$$\frac{2(2x+1)}{7}$$-5$

Question

Giải phương trình sau:
$\frac{5(x-1)+2}{6}$$-$$\frac{7x-1}{4}$$=$$\frac{2(2x+1)}{7}$$-5$

in progress 0
Kennedy 1 năm 2021-11-13T07:03:59+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-11-13T07:05:02+00:00

    Đáp án:

     `x=3`

    Giải thích các bước giải:

    `(5(x-1)+2)/6-(7x-1)/4=(2(2x+1))/7-5`

    `->(5x-5+2)/6-(7x-1)/4=(4x+2)/7-5`

    `->(5x-3)/6-(7x-1)/4=(4x+2)/7-5`

    `->(20x-12-42x+6)/24=(4x+2-35)/7`

    `->(-22x-6)/24=(4x-33)/7`

    `->-154x-42=96x-792`

    `->-250x=-750`

    `->x=3`

    Vậy `x=3`

    `cancel{nocopy//2072007}`

    0
    2021-11-13T07:05:25+00:00

    Đáp án:

    x = 3 là nghiệm của pt

    Giải thích các bước giải:

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )